Visible-light-induced sulfoxidation using chitosan-supported organic dyes photocatalyst. (February 2023) - Chen, Wei; Gu, Diankuan; Zhou, Tao; Peng, Xinwen
Abstract: Heterogeneous photocatalysts are recognized as promising candidates for photoredox reactions owing to their environmental benignity and economic efficiency. However, various functionalized organic or inorganic materials are usually utilized as carriers while not considering their complex preparation procedures and the high costs. Moreover, the catalyst loadings are not given sufficient attention. Herein, a novel recyclable photocatalyst is developed by anchoring organic dyes on biomass-derived polymers through a facile ion-exchange process. It was applied for triggering photooxidation of sulfides using air as an environmentally benign oxidant. Results show that it is a highly effective photocatalyst for selective oxidation reactions to afford a wide assortment of valuable sulfoxides. The strategy is also applicable to the synthesis of sulfoxides from alkenes and thiols. The synthetic utility of the biomass-supported organic dyes photocatalysts, together with its recoverability, reusability, and simplified purification process, renders it promising for the transformation of organic chemicals into valuable complexes. Graphical abstract: Image 1 Highlights: The QCS@RB photocatalyst was facilely prepared through the ion-exchange method. This novel composite with high RB loading (0.27 mmol/g) was obtained. The QCS@RB photocatalyst exhibits excellent activity and selectivity for the synthesis of sulfoxides. The QCS@RB photocatalyst shows good recyclability and stability.